Pharmacological Property and Cytotoxic Effect Showing Antiproliferative Potency in Human Melanoma Cell Lines (A375) of Combretum racemosum P. Beauv. Leaf and Root Extracts Used in Benin - Durand Dah-Nouvlessounon; Michaelle Chokki; Ismaël M. S. Hoteyi; Fidèle Fassinou; Floricuta Ranga; Florinela Fetea; Zorita Diaconeasa; Dan Vodnar; Bianca Furdui; Farid Baba-Moussa; Rodica Mihaela Dinica; Ramona Suharoschi; et al. (MDPI AG, 2023)
Combretum racemosum, a plant from the Combretaceae family, is traditionally used in Benin for various health problems. However, scientific research on Beninese samples of this plant is limited. The aim of this study was to identify and assess the bioactive compounds in the plant's leaves and roots. Initial screening involved analyzing powders derived from these parts for total polyphenols, flavonoids, and both condensed and hydrolyzable tannins. The polyphenolic compounds were analyzed using HPLC-DAD-ESI-MS. To evaluate the plant's antimicrobial properties, the agar diffusion method was employed, while FRAP and DPPH assays were used to determine its antioxidant capacity. For anti-inflammatory activity, the study utilized tests for in vitro protein denaturation inhibition and in vivo acute edema induced by carrageenan. Additionally, an antiproliferative assay was conducted using the human melanoma cell line A375. The analysis revealed the presence of significant polyphenolic compounds in both the leaf and root extracts of C. racemosum. Notably, compounds like Pedunculagin, Vescalagin, Casuarictin, and Digalloyl-glucoside were abundant in the leaves, with Vescalagin being especially predominant in the roots. The study also found that the dichloromethane extracts from the leaves and roots exhibited bactericidal effects on a substantial percentage of meat-isolated strains. Moreover, the antioxidant activities of these extracts were confirmed through FRAP and DPPH methods. Interestingly, the dichloromethane root extract showed strong activity in inhibiting thermal albumin denaturation, while the water-ethanol leaf extract demonstrated significant edema inhibition. Finally, the study observed that C. racemosum extracts reduced cell viability in a dose-dependent manner, with leaf extracts showing more pronounced antiproliferative effects than root extracts. These findings highlight the potential of C. racemosum leaves and roots as sources of compounds with diverse and significant biological activities. In conclusion, C. racemosum's leaves and roots exhibit promising biological activities, highlighting their potential medicinal value.